Self-Portrait (1897) by Vahram Gayfejyan and His Cafe Series of the Late 1990s – Early 1910s: A Unique Restoration Case - Sargsyan, Lilit H. (Actual Problems of Theory and History of Art, 2023)
Vahram Gayfejyan (1879–1960) — a great artist, teacher, art critic and public figure, one of the founders of art education in Armenia in the 20th century, who was formed as an artist in the Moscow avant-garde artistic environment at the beginning of the last century. In the beginning of 2022, in the National Gallery of Armenia, during the restoration of the first self-portrait of Vahram Gayfejyan, the canvas was peeled off from the cardboard, on the back of which, touching the canvas directly, a fragment of a painting was found. As a result of the studies, it was found out that the newly appeared painting represents an important piece in the series of paintings by V. Gayfejyan on the theme of cafes, created in the late 1900s and early 1910s, when the artist’s work underwent a gradual transition from Symbolism and Art Nouveau to so-called “expressionist” or “synthetic” or “neo-primitivist” style. The comparative analysis of the composition revealed a direct analogy with other similar compositions, as well as with the artist’s graphic sketches of the same years from the NGA, family, and private collections, which constituted solid grounds for attributing not only the newly appeared painting, but the series as a whole. The author also analyzes the artist’s self-portrait in the context of the development of the romantic portrait genre in the Russian and Armenian art of the 19th century and offers the most probable version of the story of the artist cropping his own work and using as a substrate for his self-portrait.
Keywords: Vahram Gayfejyan; selfportrait of Vahram Gayfejyan; Armenian painting; early 20th century; Armenian art and Russian avant-garde; cafe in painting; painting restoration; Armenian art restorers; Tatev Amirkhanyan; National Gallery of Armenia